Ber-physical system to help moor a ship - Grebeniak , Andrii (Lviv Politechnic Publishing House, 2020)
A method of organizing an information cyber-physical system to assist in the mooring process has been considered in the article. It describes ways to organize the mooring of ships to the berth. The problems that occur during this operation have been listed. As the mooring process is labor intensive and depends on the human factor, a system that will provide up-to-date real-time information to facilitate the mooring operation has been regarded. The structure and stages of development of the proposed solution have been described. The features of the selected elements have been indicated. Obtaining preliminary sensory results from two ports makes it possible to begin the next stage ofsystem development.
Keywords: moor, cyber-physical system, sensor unit